A Medicare System for Personal Healthcare Management - M, Ananthi; S, Priyanka; G, Kreethika; Shruthi S, Sai (International Journal of Engineering and Technology, 2018)
In todayâ€™s fast moving busy world, forgetfulness has become a grave concern especially the elderly and people suffering from chronic disease fail to take their medicines regularly. As per WHO (World Health Organization) it is found that nearly half of the total population do not adhere to the prescribed medication. With the advanced technology, people can be assisted for managing proper medication. This paper proposes a novel solution that uses IOT based sensor(RFID) application for Medication adherence to provide personal health care assistance. Quick counter measures are given with real time tracking of events. The developed instrumented pillbox called Medicare provides healthcare assistance on regular basis. Unlike the existing system, our device improves by providing timely remainders using load cell based on the change in weight. Also, the proposed system connects all the three healthcare players (Doctor, Patient and Pharmacy) on the same line through IoT. Our pillbox is not only restricted to seven day pill adherence but also for extended duration. This approach is easily adaptable and can impact millions of people that benefits healthcare industry.Â Â